Effect of Obesity and Family History of Cardiovascular Diseases and Diabetes Mellitus on Levels of C-Reactive Protein in Young Male - Syed Najamuddin Farooq; Ammad Ahmed; Abdul Halim S Serafi; Saeed H Halawani; Muhammad Amir Mustafa; Muhammad Irfan Safi Rizvi (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Abstract Objective: Objective of the current study was to investigate the effect of obesity and positive family history  of Cardiovascular Disease (CVD), Diabetes Mellitus (DM) on plasma C reactive protein (CRP) levels in apparently healthy young individuals. Methods: Young male Saudi students were interviewed for their personal medical and family history of Cardiovascular Disease (CVD) and Diabetes Mellitus (DM). Anthropometric parameters, height, weight, waist and hip circumference were measured. In-addition they answered perceived stress scale(PSS-14) questionnaire; Finally, Plasma C-reactive protein level was examined in all participants. Results: Results showed that the majority of our participants are overweight with mean BMI 27.113 ± 0.343 Kg/m2, but are non-stressed (24 ± 0.29). Around fifty-four per cent of participants have a positive family history of Cardiovascular Disease (CVD), Diabetes Mellitus (DM). Average Plasma CRP level was (0.267 ± 0.016 mg/dl) with 26.75% of the participants in the high-risk category. Moreover, participants that are overweight/obese and with a positive family history of Cardiovascular Disease (CVD), Diabetes Mellitus (DM) showed Significantly (P<0.0001) higher levels of Plasma hs-CRP, compared to the normal weight and with negative family history. A significant correlation was also observed between hs-CRP and BMI and WC. However, stress scores were not significantly different among different groups. Conclusion: Obesity, particularly in association with a positive family history of Cardiovascular Disease (CVD), Diabetes Mellitus (DM) or one of the two diseases is a strong predictor of low-grade systemic inflammation indicated by high plasma hs-CRP level.